Implementasi Kompetensi Guru Pendidikan Agama Islam dalam Program Sertifikasi Guru Profesional: Implementation of Islamic Religious Education Teacher Competencies in the Professional Teacher Certification Program - Wahyudi; Hasta, Muharrida; Rosdiana (ISEDU : Islamic Education Journal, 2024)
This study discusses the implementation of teacher competencies in the professional teacher certification program, which aims to improve the quality of education in Indonesia. The primary focus of this research is the application of the four main teacher competencies—pedagogical, personal, social, and professional—in the certification process, with particular attention to Islamic Religious Education (PAI) teachers. This study employs a qualitative descriptive method with a library research approach, where data is collected through a literature review of books, academic journals, and other relevant sources. Data analysis is conducted by examining, comparing, and interpreting various theories and previous research findings to gain a comprehensive understanding of the effectiveness of teacher certification. The findings indicate that certification not only enhances the quality of learning but also motivates teachers to continue their professional development through training, seminars, and further education. Certification also contributes to creating a more interactive, relevant, and conducive learning environment, thereby meeting the needs of students in the modern era. However, several challenges remain, including limited practice-based training, high administrative burdens, and restricted access to educational resources and learning technologies. Therefore, a comprehensive strategy is required, including continuous training, improved educational facilities, and periodic program evaluations to ensure that certification has a sustainable positive impact on enhancing teacher competencies and the overall quality of education at the national level.